Analisis Percepatan Gravitasi pada Ayunan Sederhana dengan Memanfaatkan PhET (Physics Education Technology) - Diah Aryati Puji Lestari; Andi Nurcahyo; Iryan Dwi Handayani (Lembaga Pengembangan Kinerja Dosen, 2024)
Physics is a part of natural science that has the properties of processes, products and values. Most of the concepts of physics are formulas, but they can be tested through experiments. Along with technological developments in experiments often used technology-based aids, for example the use of PhET (Physics Education Technology) applications to determine gravitational acceleration through simple swivel arrangements. The simple rotation experiment was performed by giving variations in rope lengths of 50 cm, 60 cm, 70 cm, 80 cm, 90 cm, and 100 cm for each of the different bulk masses of 0.5 kg and 1 kg. The study aims to determine the value of gravitational acceleration in simple rotations using PhET applications. (Physics Education Technology). Research data is displayed in tables and graphs. The data analysis uses a linear regression equation between the length of the string (L) and the square of the period (T2). Large gravitational acceleration is obtained through the gradient of the linear equation of the longness of the rope (L). The magnitude of gravitational acceleration obtained for a 0.5 kg body mass was 9.50 m/s2, for a 1 kg body weight was 9.67 m /s2, and the average perception of gravity was 9.58 m / s2.